Konversi Tindakan Sosial Pecandu Narkoba Studi Kasus Kelurahan Sijambi Tanjung Balai - Syifa Arifa Nazila Hasmi; Suheri Harahap; Neila Susanti (Sosial Simbiosis : Jurnal Integrasi Ilmu Sosial dan Politik, 2024)
This research aims to investigate the social action conversion process experienced by former drug addicts in Sijambi Village, Tanjung Balai. The case study method was used with a qualitative approach, involving in-depth interviews with a number of former drug addicts. The theory used in this research uses the theory of social action proposed by Max Weber which refers to the change or transformation of a social action from one form to another. The action conversion intended by this theory explains that social action involves a series of activities and interactions carried out by individuals or groups in society with the intention of achieving certain changes or influences. It includes active involvement in activities that have the potential to influence social norms, values, or structures. The research results show that the social action conversion process of former drug addicts in Sijambi Village involves several stages, starting from realizing there is a problem, having the motivation to change, to being involved in positive activities. First social action conversion Social action conversion is the process of changing individual or group behavior to be more positive and in line with social values. Lohan exemplifies this concept through her transformation from drug use and detrimental behavior.